Ictiofauna de riachos Neotropicais da bacia do alto rio Paraná (PR, Brasil) : estrutura e conservação. - Cionek, Vivian de Mello (2010)
Streams are characterized by unidirectional flow and its community's dependence on the input of allochtonous organic matter form the riparian zone as food and shelter source. Due to their small size, the aquatic communities that inhabit these environments, especially fish, suffer more intensely the effects of environmental fluctuations. In this context, this study aimed to identify the environmental parameters that influenced the community and fish populations in first order streams. For that purpose, three streams (Conceição, Scherer and Jurema) were sampled quarterly, from June/2008 to June/2009, using electric fishing. The paper was divided into two chapters. The first consisted of an investigation of the influence of environmental parameters on the attributes of communities. Channel Morphology, Substrate type, Riparian and Aquatic Vegetation, Anthropogenic Impacts and Water Quality, were the most relevant parameters influencing the communities studied. The second chapter embraces a population approach, investigating the influence of environmental parameters on the welfare of fish populations, through the condition factor, obtained from the length-weight relationship. Conductivity, Turbidity, Nitrate and Water Flow were the principal factors affecting the variation of fish condition in Conceição stream. In Scherer stream, the parameters were Turbidity, Area and pH. Regarding Jurema stream, the Rain, Water Temperature and Dissolved Oxygen Concentration were the most important parameters. It appears that the combination of environmental factors of each stream was decisive for the variation of fish condition. We conclude that knowledge about the most important environmental parameters on fishes constitutes an important tool to support management actions. Additionally, understanding these parameters in preserved streams can help outlying priority actions to recover those degraded.